Teknik Isolasi Protoplasma Kapang Trichoderma ssp. Menggunakan Enzim Lisis - Priyo Wahyudi; Zainal Abidin; Retno Lestari (JURNAL ILMU KEFARMASIAN INDONESIA, 2006)
Trichoderma is well known industrial fungi producing many kinds of industrial enzymes and as biological control agent. The applications of modern biotechnology using Trichoderma or its derived metabolites. Considering to the variety of the species of Trichoderma and enzymes or metabolites produced by Trichoderma lead to create a fusan of Trichoderma. The first step toward protoplast fussion is protoplasm isolation. In this experiment has been conducted protoplasm isolation of Trichoderma harzianum, T. viride, T. aureoviride and T. pseudokningii using lysing enzyme in room temperature for 1- 5 hours incubation. The aim of this experiment is to find the best condition and time of incubation in producing protoplast optimally. Trichoderma mycelia (1 mg) sink in osmotic stabilizer solution (pH 5.8), crushed and add 1 ml lysing enzyme 2%, then incubate in shaker incubator (room temperature) for 5 hours. Observation of the protoplast is conducted using haemacytometer for 1 until 5 hours incubation. After 5 hours incubation in room temperature showed the T. harzianum protoplast is the highest number of protoplast (40,150 protoplast/ml), followed by T. pseudokoningii (10,375 protoplas/ ml), T. viride (15,075 protoplast/ml) and T. aureoviride (10,050 protoplas/ml).